Transient Neonatal Cholestasis Secondary to Coagulase-negative Staphylococci Septicemia: A Case Report - Suneel K Kommineni; Singamala Rufus Rajkumar; Preethi Subramanian; Chitgupikar Sudharshan Raj (Pediatric Infectious Disease)
Transient neonatal cholestasis (NC) is characterized by early-onset cholestasis and normalization of clinical and biochemical parameters at follow-up. The causes are multifactorial and include immature bile secretion (as in the case of prematurity) and other perinatal causes. Sepsis is responsible for 20% of cases of NC. It is mandatory to rule out other causes of NC before labeling the neonate as having transient NC. The use of ursodeoxycholic acid in cholestasis has been advocated to bring a faster decline in direct bilirubin levels in neonates. Neonates have to be evaluated early considering associated risk factors so that early intervention could prevent complications and yield better outcomes.